Role of ferroptosis in pregnancy related diseases and its therapeutic potential - Xu, Jinfeng; Zhou, Fan; Wang, Xiaodong; Mo, Chunheng (Frontiers in Cell and Developmental Biology, 2023)
Ferroptosis is a form of regulated cell death characterized by iron overload, overwhelming lipid peroxidation, and disruption of antioxidant systems. Emerging evidence suggests that ferroptosis is associated with pregnancy related diseases, such as spontaneous abortion, pre-eclampsia, gestational diabetes mellitus, intrahepatic cholestasis of pregnancy, and spontaneous preterm birth. According to these findings, inhibiting ferroptosis might be a potential option to treat pregnancy related diseases. This review summarizes the mechanisms and advances of ferroptosis, the pathogenic role of ferroptosis in pregnancy related diseases and the potential medicines for its treatment.